Analytical method to study multiple scattering characteristics in participating media. (October 2016) - Zhang, Chuan-Xin; Yuan, Yuan; Li, Tian-Jiao; Dong, Shi-Kui; Tan, He-Ping
Highlights: An analytical method to determine arbitrary-order scattering is proposed. Apparent directional radiative intensity as a function of scattering order is calculated. The concept of a "backward optically thick medium" is presented. Abstract: The radiative transfer and characteristics of multiple scattering in participating media are critical issues in the fields of atmospheric research and target detection. In this work, the apparent directional radiative intensity distribution influenced by multiple scattering is deduced using angle discretization in a computational domain and path integrals in the direction of transmission. The multiple scattering analytical method (MSAM) is used to determine the apparent directional radiative intensity distribution influenced by multiple scattering in participating media. The apparent directional radiative intensity as a function of the scattering order is calculated. The forward and backward scattering energies, which vary with the optical thickness, are determined using the above-mentioned method and model. The computational accuracy, efficiency, and applied range of the MSAM differ from those of the Monte Carlo method. The forward and backward scattering energy changes with the optical thickness for different scattering orders. Thus, the concept of a "backward optically thick medium" is proposed based on this. The current work perfects the multiple scattering theory. The results obtained are important for quick estimations of the main radiative characteristics of participating media.